OPTIMALISASI POTENSI DANA ZAKAT, INFAQ, SADAQAH DALAM PEMERATAAN EKONOMI DI KABUPATEN SUKOHARJO (Studi Kasus di Badan Amil Zakat Daerah Kab. Sukoharjo) - Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2017)
Economic activity is something that can not be separated from human life especially good for a country or region. Along with the times, of the needs of humans increase therefore the economy is continuously growing and changing. Islamic philanthropy has an important role in the economy. an instrument of philanthropy is the mechanism of transfer of the rich to the poor is right on target. At the same time, the Islamic philanthropy instrument acts as an effective social safety net. With the transfer of income from the rich to the poor, there will be an increase in demand for goods and services from the poor, who are generally basic needs. Judging from the type of funding source, Zakat, Infak, Sadaqah (ZIS) with the largest Muslim population in the world, Indonesia has the potential for enormous ZIS. The methodology in this study used a qualitative phenomenological approach, so that research results in accordance with the facts on the ground. Source of data derived from primary data and secondary data. While data collection techniques with in-depth interviews, documentary studies, as well as participant observation. Potential national charity reached 19.3 trillion. While Hafidhuddin (2010), said that the potential of zakat in Indonesia reached 80 trillion annually (this potential, before accounting for the funds infaq and sadaqah untapped in the community as a source of funds are voluntary sadaqah infaq. Potential Zakat, Infaq, Shodaqoh Sukoharjo regency of 1.6 M / year average of 30% in the form of zakat profession dominated by civil servants and the percentage of individuals still need to be improved and 70% is still a infaq shodaqoh